Gamifikasi dalam Pemrograman CNC: Pengaruh terhadap Perolehan Keterampilan dan Motivasi dalam Lingkungan Pembelajaran Berbasis Simulator - Julianto Wahyudi, Dian; Wayan Dika, Johan; Efendi, Adhan (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2025)
This study evaluates the effectiveness of integrating gamification into CNC programming instruction using the CAMotics simulator. Twenty-eight Mechanical Engineering students participated in a four-week gamified intervention combining leveling, points, badges, instant feedback, and leaderboards. Data were collected through pre/post-tests, motivation questionnaires, and simulator log metrics (time-on-task, error rate, and revisions). Results show significant improvements in post-test scores (p < 0.001) and substantial reductions in completion time and syntax errors (Cohen’s d > 2.8). Motivation scores also increased, with intrinsic motivation positively correlating with technical performance. Theoretically, this study extends technology-enhanced learning by positioning simulator log data as a performance-based evaluation framework for vocational gamification design. Although the study was conducted without a control group, the findings provide preliminary evidence of the effectiveness of gamified simulator learning in vocational engineering contexts. Practically, it offers an evidence-driven model for integrating digital gamified learning into mechanical engineering education.